Encouraging help-seeking and engagement in a mental health app: What young people want - Sandra Garrido; Eliza Oliver; Anthony Chmiel; Barbara Doran; Katherine Boydell; Katherine Boydell (Frontiers Media S.A., 2022)
Although many young people evince a preference for digital mental health support over face to face, engagement with smartphone apps for mental health remains relatively low, particularly in young people not accessing professional support services. While some of this can be attributed to stigma or embarrassment, there is also a need for developers and researchers to investigate features which promote long-term usage. MoodyTunes is a music-based smartphone app that has been co-designed with young people to help them develop effective self-management strategies for mood through music listening. Four focus groups with young people (N = 24, aged 13-25) were conducted to workshop how MoodyTunes could promote help-seeking behaviours and long-term engagement with the app. Online discussions following a broad topic guide were held in groups of 4-7 in which participants explored topics including the use of social features, promoting help-seeking behaviour, gamification and mood tracking. Participants also viewed visual materials and offered ideas about visual design both verbally and on paper. A general inductive approach was taken to analysis of qualitative data. Three primary themes were identified in the data: privacy; user empowerment; and engagement vs. achievement. Participants voiced a strong desire to remain anonymous and to feel empowered to make their own decisions about accessing professional help. Sensitive use of language was noted as critical, with some participants noting that the use of more directive language could have a negative impact on their mental health and that motivational features should focus on engagement with the primary aim of the app rather than rewarding achievement. Findings highlight the benefits of a co-design approach and provide key insights into how mental health apps may be able to improve long-term user engagement with young people.